2022
DOI: 10.1186/s12931-022-01960-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ambient temperature and adult asthma hospitalizations in Beijing, China: a time-stratified case-crossover study

Abstract: Background Studies on the associations between ambient temperature and asthma hospitalizations are limited, and the results are controversial. We aimed to assess the short-term effects of ambient temperature on the risk of asthma hospitalizations and quantify the hospitalization burdens of asthma attributable to non-optimal temperature in adults in Beijing, China. Methods We collected daily asthma hospitalizations, meteorological factors and air qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 56 publications
5
27
0
1
Order By: Relevance
“…This approach accounts for the potentially complex temporal patterns of exposure–response relationships to provide more appropriate estimates for the disease burden, and thus has been widely used in previous studies within the framework of DLNM. 7 , 17 , 22 , 25 The formulas of backward attributable fraction (AF) and number (AN) at time t were as follows 24 : …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach accounts for the potentially complex temporal patterns of exposure–response relationships to provide more appropriate estimates for the disease burden, and thus has been widely used in previous studies within the framework of DLNM. 7 , 17 , 22 , 25 The formulas of backward attributable fraction (AF) and number (AN) at time t were as follows 24 : …”
Section: Methodsmentioning
confidence: 99%
“… 24 The corresponding 2.5 th and 97.5 th percentiles of the distributions by simulating 5000 random samples were interpreted as the 95% eCIs. 22 , 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, Monte Carlo simulations were used to calculate empirical confidence intervals (eCIs) by assuming a multivariate normal distribution of point estimates and a variance matrix derived from the regression model (Gasparrini and Leone 2014). A random sample of 1000 was simulated, corresponding to 2.5th and 97.5th was interpreted as 95% eCIs (Chen et al 2022;Gasparrini and Leone 2014;Tian et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As metabolic disease fractions attributable to outdoor ALAN, using the backward method from a previous study, we quantified the presence of metabolic disease due to outdoor ALAN (Gasparrini and Leone 2014), and exposures from the past 30 days could be summarized in this way. This approach takes into account potentially complex temporal patterns of exposure-response relationships, thus providing a more appropriate estimate of disease burden, and has therefore been used extensively in previous studies within the DLNM framework (Chen et al 2022;Fu et al 2018;Tian et al 2016;Yang et al 2017). We calculated the attribution fractions (AF) for metabolic disease at outdoor ALAN exposure of 0, 10, 20 nWcm −2 sr −1 for different sex and age groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Another study found a complex U-shaped association between asthma disease burden and temperature. 27 Small real-world studies demonstrated that increased pollen exposure was associated with an increased prevalence of asthma exacerbations. 28 …”
Section: Introductionmentioning
confidence: 99%